Calcium in a supernova remnant as a fingerprint of a sub-Chandrasekhar-mass explosion - Das, Priyam; Seitenzahl, Ivo R.; Ruiter, Ashley J.; Röpke, Friedrich; Pakmor, Rüdiger; Vogt, Frédéric P. A.; Collins, Christine E.; Ghavamian, Parviz; Sim, Stuart A.; Williams, Brian J.; Taubenberger, Stefan; Laming, J. Martin; et al. (Nature astronomy, 2025)
Type Ia supernovae play a fundamental role as cosmological probes of dark energy and produce more than half of the iron in our Galaxy. Despite their central importance, a comprehensive understanding of their progenitor systems and triggering mechanism is still a long-standing fundamental problem. Here we present high-resolution integral field spectroscopic observations of the young supernova remnant SNR 0509-67.5 in the Large Magellanic Cloud. We uncover a double-shell morphology of highly ionized calcium [Ca XV] and a single shell of sulphur [S XII], observed in the reverse shocked ejecta. Our analysis reveals that the outer calcium shell originates from the helium detonation at the base of the outer envelope, while the inner shell is associated with the carbon-oxygen core detonation. This morphological distribution of intermediate-mass elements agrees qualitatively with the predicted signature of the double detonation of a sub-Chandrasekhar-mass white dwarf from a hydrodynamical explosion simulation. Our observations reveal two distinct, spatially separated peaks in surface brightness of [Ca XV] from the supernova remnant phase, providing substantial evidence that sub-Chandrasekhar-mass explosions through the double-detonation mechanism could occur in nature. They also highlight the importance of remnant tomography in understanding explosion mechanisms from the remnant phase.
Veröffentlicht: 02. Juli 2025
Gesehen am 10.11.2025